2020
DOI: 10.1074/jbc.ra119.011688
|View full text |Cite
|
Sign up to set email alerts
|

MtrP, a putative methyltransferase in Corynebacteria, is required for optimal membrane transport of trehalose mycolates

Abstract: Pathogenic bacteria of the genera Mycobacterium and Corynebacterium cause severe human diseases such as tuberculosis (Mycobacterium tuberculosis) and diphtheria (Corynebacterium diphtheriae). The cells of these species are surrounded by protective cell walls rich in long-chain mycolic acids. These fatty acids are conjugated to the disaccharide trehalose on the cytoplasmic side of the bacterial cell membrane. They are then transported across the membrane to the periplasm where they act as donors for other react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…This hTMCM/h2TDCM phenotype is similar to that originally described for ∆tmaT (NCgl2759) [17,27] and ∆mtrP (NCgl2764) [18] mutants. We previously showed that loss of TmaT and MtrP led to global changes in the lipidomes of mutant lines [18,27].…”
Section: A ∆Ncgl2761 Mutant Phenocopies ∆Tmat and ∆Mtrp Mutantssupporting
confidence: 85%
See 3 more Smart Citations
“…This hTMCM/h2TDCM phenotype is similar to that originally described for ∆tmaT (NCgl2759) [17,27] and ∆mtrP (NCgl2764) [18] mutants. We previously showed that loss of TmaT and MtrP led to global changes in the lipidomes of mutant lines [18,27].…”
Section: A ∆Ncgl2761 Mutant Phenocopies ∆Tmat and ∆Mtrp Mutantssupporting
confidence: 85%
“…This hTMCM/h2TDCM phenotype is similar to that originally described for ∆tmaT (NCgl2759) [17,27] and ∆mtrP (NCgl2764) [18] mutants. We previously showed that loss of TmaT and MtrP led to global changes in the lipidomes of mutant lines [18,27]. To investigate whether similar changes also occurred in the ∆NCgl2761 mutant line, we undertook a detailed analysis of the IM and OM lipid extracts of the WT and mutant strains by LC-ESI-QTOF-MS in positive ionization mode (Figure 6).…”
Section: A ∆Ncgl2761 Mutant Phenocopies ∆Tmat and ∆Mtrp Mutantssupporting
confidence: 85%
See 2 more Smart Citations
“…To investigate whether fmt encodes a methyltransferase, the amino acid sequence of Fmt was aligned with other validated methyltransferases using CLUSTALW (https://www.genome.jp/tools-bin/clustalw). The aligned sequences include MT0146/CbiT from Methanobacterium thermoautotrophicum 42 , the corynebacterial MtrP protein (NCg12764) assisting the transport of trehalose mycolates 43 , the methyltransferase catalyzing the transfer of a methyl group onto the lipid moiety of phthiotriol and glycosylated phenolphthiotriol dimycocerosates in M. tuberculosis (Rv2952) 44 and the Fmt orthologue in M. smegmatis Mtf2 45 , for which active site residues have been identified. In particular, two glycine residues are conserved in S-adenosyl methionine (SAM)dependent methyltransferase and known to be involved in binding to the methyl donor.…”
Section: Figure 2 Generation Of An Unmarked Fmt Deletion Mutant In Mmentioning
confidence: 99%